What Drives Continuous Viewing of Short Form Drama? The Role of Viewing Motivation and Flow Experience - Mufidatul Azmi; Muhaidir Ikram; Nidrah (Economics and Business Journal (ECBIS), 2026)
The rapid expansion of short-form video platforms has reshaped the way audiences engage with digital entertainment. Among these formats, short-form drama has emerged as a distinctive narrative genre characterized by episodic storytelling within brief viewing durations. Despite its increasing popularity, empirical research explaining the psychological mechanisms underlying Continuous Viewing Intention in short-form drama remains limited. This study investigates the influence of Viewing Motivation on Flow Experience and Continuous Viewing Intention. In this study, Viewing Motivation is conceptualized as a higher-order construct comprising Performance Expectancy, Social Influence, Hedonic Motivation, Habit, Substitute Expectancy, and Aesthetic Motivation. Data were collected through an online survey involving 140 respondents in Makassar who actively consume short-form drama content. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that Viewing Motivation significantly influences both Flow Experience and Continuous Viewing Intention. Furthermore, Flow Experience significantly affects Continuous Viewing Intention and mediates the relationship between Viewing Motivation and Continuous Viewing Intention. These findings underscore the importance of motivational drivers and immersive viewing experiences in fostering sustained engagement with short-form drama content